Detection of Thiopurine S-Methyltransferase (TPMT) Polymorphisms TPMT*3A, TPMT*3B and TPMT*3C in Children with Acute Lymphoblastic Leukemia - Mohammed, Nawar S.; Rasheed, Manal K.; Ghali, Hasanein H.; Ahmed , Shaymaa J. (Journal of the Faculty of Medicine Baghdad, 2018)
Background: Thiopurines are essential medications in Acute Lymphoblastic Leukemia (ALL) treatment protocols as anti-cancer agents since long time; however, their use might result in unexpected toxicities in ALL children due to the low thiopurine S-methyltransferase (TPMT) activity, a major enzyme involved in 6- mercaptopurine metabolism, which strongly correlates to the genetic polymorphism of the TPMT gene in those patients. Objective: To identify the most common TPMT polymorphisms in children with ALL and its frequencies. Methods: A cross sectional study enrolling eighty-one ALL children receiving mercaptopurine drug during their maintenance course of treatment according to UKALL – 2011 protocol, were enrolled in this study. After DNA extraction from whole blood TPMT genetic polymorphisms were detected by allele-specific multiplex-PCR analysis. Results: A total of 51 children with allele frequencies of (62.96%) were homozygous for the wild-type allele TPMT*1, 30 children with allelic frequency of (37.03%) were heterozygous for one of the two mutant alleles (TPMT*3A or TPMT*3C) with allele frequencies of 29.62% and 7.4% respectively, while no result was found homozygous for two mutant alleles or TPMT*3B allele. Conclusions: This is the first study in Iraq to identify the genetic polymorphism of TPMT in a group of ALL children being treated for ALL. The study revealed the presence of TPMT*3A and TPMT*3C genetic polymorphisms among the study sample, no TPMT*3B was identified in the study sample.